PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT. ELANG REAKSI CEPAT, JAGAKARSA JAKARTA SELATAN - Puspita Fitriani; Ihwan Satria Lesmana; Ombi Romli (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Based on the results of initial observations obtained from PT. Elang Reaksi Cepat, information was obtained that one of the problems that must be resolved at this time is how to encourage employees to further improve their performance. It was informed that the performance conditions of employees at PT. Elang Reaksi Cepat is still low. The aim of this research is to determine the partial and simultaneous influence of work motivation and work environment on employee performance at PT. Elang Reaksi Cepat, Jagakarsa, South Jakarta. The method used in this research is a survey method, using a quantitative correlational approach, namely looking at cause-and-effect relationships. The sample used was part of the population in this study, namely 78 employees using a saturated sample. This research can be concluded either partially or simultaneously, work motivation and work environment have a significant effect on employee performance at PT. Elang Reaksi Cepat, Jagakarsa, South Jakarta.